Spostando la Grecia a Est: Uchtomskij e il viaggio dello carevič Nicola - Martina Morabito (eSamizdat)
In 1893 the prince Esper Esperovich Ukhtomsky published “Puteshestvie na Vostok”, the account of an extended trip undertaken in 1890-91 by the young Nikolay Alekseyevich, the future Nicholas II, who was then heir to the Russian throne. Greece was the first stopover on a trail that subsequently wound through India, Ceylon, Java, Siam, Japan and China. Ukhtomsky's account of this venture, in which he participated, underlines a connection between Greece and Asia that is the subject of this paper. In Ukhtomsky's view, Ancient Greece had a profound link to the East and therefore, through a connection between the Hellenic and Orthodox Slavic worlds, Ancient Greece was also linked to Russia. Specifically, he argues that Russia's future lies in the East. This paper argues that Ukhtomsky's travelogue contributed to a general repositioning of Greece within the Russian cultural imaginary at the turn of the 19th century.